Saying ?no? to temptation want-to motivation improves self-regulation by reducing temptation rather than by increasing self-control. [article]. - Milyavskaya, Marina; Inzlicht, Michael
Self-regulation has been conceptualized as the interplay between controlled and impulsive processes; however, most research has focused on the controlled side (i.e., effortful self-control). The present studies focus on the effects of motivation on impulsive processes, including automatic preferences for goal-disruptive stimuli and subjective reports of temptations and obstacles, contrasting them with effects on controlled processes. This is done by examining people's implicit affective reactions in the face of goal-disruptive "temptations" (Studies 1 and 2), subjective reports of obstacles (Studies 2 and 3) and expended effort (Study 3), as well as experiences of desires and self-control in real-time using experience sampling (Study 4). Across these multiple methods, results show that want-to motivation results in decreased impulsive attraction to goal-disruptive temptations and is related to encountering fewer obstacles in the process of goal pursuit. This, in turn, explains why want-to goals are more likely to be attained. Have-to motivation, on the other hand, was unrelated to people's automatic reactions to temptation cues but related to greater subjective perceptions of obstacles and tempting desires. The discussion focuses on the implications of these findings for self-regulation and motivation.. -- (from the authors)